2020
DOI: 10.1016/j.placenta.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of using nanotherapy during pregnancy: Technological aspects and biomedical implications

Abstract: During the period of pregnancy, several processes and physiological adaptations occur in the body and metabolism of pregnant woman. These physiological adaptations in pregnant woman end up leading to a suppression in immune system favoring obstetric complications to the mother, fetus and placental tissue. An effective pharmacological therapy for these complications is still a challenge, since some drugs during pregnancy can have deleterious and teratogenic effects. An emerging alternative to pharmacological th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Indeed, the rational and well-planned design of nanosystems, necessary to ensure their safety for obstetric use, cannot be independent of an in-depth understanding of the aforementioned factors. Researchers are nowadays focusing on the development of innovative nanoparticles to answer the specific needs of pregnancy disorders [109]. To go further, it could be interesting to design new nanosystems such as targeting nanoparticles, such as liposomes, for placental MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the rational and well-planned design of nanosystems, necessary to ensure their safety for obstetric use, cannot be independent of an in-depth understanding of the aforementioned factors. Researchers are nowadays focusing on the development of innovative nanoparticles to answer the specific needs of pregnancy disorders [109]. To go further, it could be interesting to design new nanosystems such as targeting nanoparticles, such as liposomes, for placental MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Shojaei and coworkers reviewed the literature in detail on different placental models and the fetal risk assessment, considering various organic and inorganic nanoparticles [ 36 ]. Inorganic nanoparticles have been demonstrated to easily cross the blood–placental barrier and induce several toxicological effects [ 59 ]. In contrast, organic nanoparticles can be more selective in their target potential and show less toxicological effects [ 18 , 59 ].…”
Section: The Placental Barrier Therapeutic Perspectives Of Nanopartic...mentioning
confidence: 99%
“…Placenta functions to exchange oxygen, nutrients, metabolic waste, and other molecules between the maternal and fetal bloodstream [49]. Factors that control the transfer of substances between maternal and fetal circulation include membrane surface area and thickness, blood flow, hydrostatic pressure in the intervillous chamber and the difference between fetal and maternal osmotic pressure [50]. Beside the placenta, amnion, chorion and parietal decidua also surround the fetus.…”
Section: Translocation Of Nanoparticles Through the Placentamentioning
confidence: 99%
“…NPs with diameters 1-100 nm have been shown to transverse the placental barrier and were detected in the brain of the offspring [57,58]. Gestational age is an important factor affecting the toxicity of NP on the fetus [50]. Fennell et al [59] have demonstrated that AgNP administered through oral and IV route on gestational day 18 resulted in placental accumulation after 48 h. Campagnolo et al [60] demonstrated that inhalation of Ag NP during the first gestational day until the fifteenth gestational day in female rats caused fetal resorption.…”
Section: Translocation Of Nanoparticles Through the Placentamentioning
confidence: 99%